The Concept Of Worship From IBN Taymiyyah's Perspective - Septiyan Dwi Putra; Muhammad Azrul Amirullah (CV. ITTC INDONESIA, 2025)
This paper discusses worship, which is a means of connecting a servant with Allah SWT, starting from the heart, tongue, to the limbs. There is almost no difference of opinion among scholars regarding these three things to carry out worship rituals. Basically, worship is a very important matter to discuss because the origin of worship is in accordance with the guidance of the Qur'an and hadith, so that if the worship ritual is not in accordance with the Qur'an and hadith then the law is haram or forbidden which can lead to invalidity in its implementation. One of the famous scholars or mujtahid who has become a reference for many Muslims is Ibn Taimiyyah. This study uses secondary data sources that use several journals, magazines, newspapers, articles, books written by Ibn Taimiyyah related to the title of this research and other literature related to this research. The result according to Ibn Taimiyyah is truly carrying out what has been determined by Allah SWT, because in taking sources of religious teachings in general for worship is tauqiifiyyah (dependent on revelation). This means that it is impossible to determine any problem in aqidah other than the Al-Qur'an and As-Sunnah, as well as the agreement (Ijma') of the Salaf, because their agreement is protected from error. Then, according to Ibn Taymiyyah, every person who is Muslim must adhere to two main principles when worshiping. First, worship is performed only to Allah SWT.